A Cross Country Analysis of Financial Conditions and Earnings Management - Firdaus Kurniawan; Nandya Octanti Pusparini; Hilma Tsani Amanati; Albertus Henri Listianto Nugroho (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2022)
This study aims to examine the effect of the company's financial condition on the earnings management behavior of companies in the Asian region. This study extends the existing research model by presenting a cross-country analysis of the relationship of financial conditions, which is specifically divided into three zones, namely financial distress, gray zone, and excellent financial condition, with corporate earnings management. The sample in this study consists of companies listed on stock exchanges of countries in Asia, with an observation period from 2009 to 2019. This study provides empirical evidence that supports the relationship between financial condition and company earnings management, which shows that earnings management is used as a tool by the management of companies that are under financial pressure to distort the quality of reported information, thereby creating a bias in the interpretation of company performance. This study proves that the characteristics of the company's financial condition, both in the safe zone, gray zone, and excellent zone, affect the pattern of company earnings management practices. This study measures earnings management using the discretionary accrual method so that it only captures earnings management practices that are part of the company's discretionary accrual management policy. Research can study earnings management further with the real earnings management approach to examine the effect of the company's financial condition on the distortion of earnings information through the company's actual activities.